Organizational Performance Measures - Methodology of Improvement and Productivity Assessment Model in Polish Manufacturing and Logistics Companies - Renata PIĘTOWSKA-LASKA (Communications of International Proceedings, 2022)
The article analyses the role and importance of productivity as a measure of organizational efficiency, the level of which, as shown by the experience of developed countries, is an important factor in increasing the competitiveness of enterprises. The aim of the study was to diagnose current trends and approaches to improving productivity in Polish manufacturing and logistics companies. The article presents a new approach to improving productivity in a manufacturing company, based on a rich set of concepts, methods and techniques in the field of production management. Improvement of productivity is a complex technical, organizational and social undertaking, implemented in order to increase the efficiency of the entire enterprise. This approach assumes continuous improvement of productivity in all phases of the design and operation of the production system. Currently, a strategic, holistic approach to improving productivity is gaining in importance, expressed in the desire to implement modern, comprehensive management concepts. The result of the analysis is the development of a productivity improvement methodology that takes into account new production paradigms, including: Lean Manufacturing, Lean Logistics, Agile Manufacturing, Total Productivity Maintenance, Theory of Constraints and Dynamic Process Management. The methodology for evaluating the efficiency of the logistics system was also presented. The conclusion of the work emphasizes the role and importance of the productivity of logistics systems, which in the modern world is becoming one of the sources of economic growth, social progress and improving the standard of living. The result of the analysis is the development of a multi-level model of the productivity assessment system in logistics. The conclusion emphasizes the importance of developing a new productivity improvement methodology and a productivity assessment model for improving production and logistics management practices aimed at increasing productivity.
Keywords: organizational performance measures; productivity; productivity improvement methodology; productivity assessment model; manufacturing and logistics companies